Equity: The Actors' Trade Union - Gemmill, Paul F. (Quarterly Journal of Economics, 1926)
I. The Actors' Equity Association formed in 1913. — Affiliation with the Federation of Labor, and successful strike of 1919, 130. — Maneuvers of the managers, 132. — Virtually a closed-shop situation emerged, 133. — II. Complete success of the actors and their gains, 135. — The contract of 1924 distinctly a minimum contract, 139. — III. Further consideration of the contract, 140. — Benefits to the managers, and disciplinary power of Equity, 141.